Our way or the highway : inside the Minnehaha Free State - Losure, Mary (University of Minnesota Press, 2002)
Construction plans for the reroute of Highway 55 through south Minneapolis sparked an environmental movement that pitted activists against public authorities in one of the most dramatic episodes in the citys history. Fueled by idealism and anger, a diverse coalition of Native Americans, neighborhood residents, and young anarchists banded together to try to stop the highway expansion. Beginning in 1998, this group sustained protests for more than a year and eventually faced an unprecedented show of force by law enforcement.